The Official Recommendations Proposed to Replace Anglicisms in the Petit Robert de la langue française - Niklas-Salminen, Aïno (Kalbotyra, 2021)
The dictionary Petit Robert leads a fight against both the single thought and the impoverished expression by offering a very broad vision of the practices of French. A certain number of anglicisms, very frequent among the new entries of this dictionary, are considered questionable, insofar as the prestige and the economic and techno-scientific power of the United States give rise to a wave of borrowed words, even when the lexicon has suitable French synonyms. The Petit Robert indicates which words in French are recommended by the Commission générale de la terminologie et de néologie to replace the anglicisms. The objective of this study is to observe the English words recently introduced in this dictionary and the different French equivalent terms proposed to oust them. Could the official recommendations supplant the loanwords and become fixed in practice?